Dam of the Kolyma Hydroelectric Power Plant (Plotina Kolymskoi Ges) - Petrov,V G; Losev,E D (1976)
This report discusses the variety of problems and conditions which complicated the planning and construction of the Kolyma Hydroelectric power plant. This report was written before actual construction began. (Author) Trans. of Vsesoinznyi Proektno-izyskatel'skii Nauchno-issledovatel'skii Institut 'Gidroproekt'. Trudy Gidroproekta (USSR) n34 p78-87 1973.